Distributed Precoder Design for Uplink TDD MU-MIMO Systems - Dong, JiYu; Sun, Yi; Fu, Rong; Zhao, ChunMing; Jiang, Ming (2022 IEEE 8th International Conference on Computer and Communications (ICCC), 2022)
In the existing designs for uplink multi-user Multiinput Multi-output (MU-MIMO) systems, centralized schemes usually provide good performance where the precoder is com-puted by the base station (BS) and then fed back to each terminal. However, this brings huge amounts of feedback overhead and therefore is hard to implement. The 5G protocol supports the use of the uplink codebook to deploy a precoder, hence the feedback cost is significantly compressed by transmitting only the index. In this letter, we develop a novel distributed precoder design for the uplink time division duplex (TDD) MU-MIMO systems subject to the transmit power constraint in terms of each terminal or each antenna. Taking both the error rate performance and the feedback overhead into account, the proposed scheme allows each terminal to obtain its own precoder based on the alternating optimization. Under the distributed strategy, no precoder feedback is required for the system, while with acceptable performance loss. In addition to the analysis, simulation results are presented to validate the effectiveness of the proposed scheme.